(untitled) (Economics and region, 2023)
In the article, an economic study of the limits of the effectiveness of managing the innovative development of the economy in conditions of global uncertainty is carried out. The formation and development of modern Ukrainian society requires prompt access to the necessary innovative resources. It is noted that the transition to an innovative type of development opens up not only great prospects, but also creates significant risks for the stability and balance of development itself. It was found that innovative development for the state is both a source of uncertainty and a tool for removing uncertainty. That is, every phenomenon and process requires an in-depth analysis of the entire complex of their causes and consequences, which usually turn out to be complex and contradictory, going beyond both individual directions of economic thought and the economic field of research in general. It has been proven that our state at this stage should rely on realistic ideas about the insufficient effectiveness of the existing institutes of innovative development. The deep problems of strategy and tactics of reforms, which prevent the formation of the institutional system of the national economy of the innovative type, are identified. The peculiarities of the need to learn about the institutional dimension of the innovative economy, to overcome existing institutional pitfalls in the process of introducing innovative technologies, are analyzed. The institutional components of innovation spheres and institutional mechanisms of innovative development are proposed. It was established that this process led to the intensification of the search for conceptual factors of the effectiveness of management of modern innovative trends. The necessity of introducing new mechanisms of the national innovative path of self-development has been proven. It was determined that the question of the influence of the economic power of the state on the search for effective mechanisms of the effectiveness of managing the innovative development of the economy in the conditions of global challenges remains unresolved.